Primer de Maig : 1937 : poesies
Contiene poesías políticas de Miguel Hernández, Clementina Arderiu, Rafael Alberti, Joan Maragall, Federico García Lorca, Ventura Gassol, Juan Ramón Jiménez, Apeles Mestres y A. Esclasans